Peripheral–central immune interactions in Parkinson’s disease: insights into innate and adaptive immunity - Tumpa, Jarika Jahan; Hayder, Qurat Ul Ain; Maisa, Nowshin Sharmily; Islam, Md. Nazmul (Frontiers in Molecular Neuroscience, 2025)
Parkinson’s disease (PD) is a complex, multisystem disorder characterized by chronic inflammatory processes. The development of effective immunomodulatory therapies for PD requires a novel and comprehensive understanding of the coordinated interactions between central and peripheral innate and adaptive immune responses that are initiated and evolve throughout disease onset and progression. Immune system dysregulation is a defining feature of PD, with a substantial body of evidence indicating pathological alterations in both central and peripheral immune responses that evolve dynamically over the course of the disease. In PD, central inflammation is defined by the activation of astrocytes, microglia and T-cell responses within the central nervous system. In contrast, peripheral inflammation involves the activation of T-cell signaling and innate immune cells in the enteric nervous system, circulatory system and gastrointestinal tract. However, the underlying mechanisms of this inflammation in PD-associated diseases remain unclear, and identifying the initial stages of these diseases is a major unmet need. This review seeks to address this question by highlighting and discussing the central and peripheral systems through the collection of current data from clinical evidence and findings from experiments.